Civil Society Organizations’ Participation in the EU and Its Challenges for Democratic Representation - Nicolle Zeegers (Politics and Governance, 2016)
Online consultations and the European Citizens’ Initiative (ECI) are tools that have been put into place by the European Union (EU) in order to increase the participation of citizens and Civil Society Organizations (CSO) in its politics and policy making. The current CSO representation at the system level of the EU is claimed to be biased in favor of the interests of economic producers and CSOs coming from old member states. The central question of this article is whether these tools help make participation more representative of the diversity of societal groups within the EU. The concept of ‘actor representativeness’ as well as ‘discourse representativeness’ will be applied in order to answer this question.